Schools as racial spaces: understanding and resisting structural racism. Issue 2 (7th February 2016) - Blaisdell, Benjamin
Abstract : Analyzing schools as racial spaces can help researchers examine the role of teachers in the perpetuation of structural racism in schools. Based on ethnographic and autoethnographic work, this article offers examples of schools as racial spaces, spaces where whiteness controlled access. It also highlights four teachers who pursued racial equity in their teaching, and how a structural understanding of race was key to their efforts. It makes the argument that racial spaces analysis can help researchers work with teachers to understand structural racism and to better counter it in school practices.